2016
DOI: 10.1042/cs20160069
|View full text |Cite
|
Sign up to set email alerts
|

IL-10-producing regulatory B-cells suppressed effector T-cells but enhanced regulatory T-cells in chronic HBV infection

Abstract: Non-specific immune responses to antigens have been demonstrated as being enhanced during chronic hepatitis B virus (HBV) infection. Here, we evaluated the role of interleukin-10 (IL-10)-producing regulatory B-cells (Bregs) in the pathogenesis of HBV-related liver fibrosis (HBV-LF) and assessed their immunoregulatory effects. Sixty-seven patients diagnosed with chronic hepatitis B (CHB) were enrolled in this study. Numbers and frequencies of peripheral B-cells (memory CD19(+)CD24(hi)CD27(+) cells, immature/tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(68 citation statements)
references
References 33 publications
3
61
0
1
Order By: Relevance
“…Liu et al. observed that, in chronic hepatitis B virus infection, regulatory B cells could enhance regulatory T cell function and influence immune tolerance . Whether regulatory T cells and regulatory B cells underwent synergistic interactions in maintaining UVB‐induced immunosuppression was still undetermined in our study.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Liu et al. observed that, in chronic hepatitis B virus infection, regulatory B cells could enhance regulatory T cell function and influence immune tolerance . Whether regulatory T cells and regulatory B cells underwent synergistic interactions in maintaining UVB‐induced immunosuppression was still undetermined in our study.…”
Section: Discussionmentioning
confidence: 64%
“…However, because of the lack of regulatory T cell depletion experiments in our study, we cannot exclude a suppressive role of regulatory T cells in our research model. Sun immune tolerance (36). Whether regulatory T cells and regulatory B cells underwent synergistic interactions in maintaining UVB-induced immunosuppression was still undetermined in our study.…”
Section: Discussionmentioning
confidence: 71%
“…Treg cells could release CTLA-4, IL-10, and other immune mediators/molecules to resist the invasion of Teff and antigen-presenting cells to modulate the local microenvironment. 34 However, the function of Treg cells in acute infections has not been elucidated. Some scientists found that patients infected with influenza A virus might have an accumulation of Treg cells.…”
Section: Treg% Does Not Differ Between Infected and Uninfected Patientsmentioning
confidence: 99%
“…a,b). The Breg cells can induce Foxp3 + Treg cells to perform inhibitory functions . Therefore, we examined the CD4 + CD25 + Foxp3 + Treg cell frequencies in peripheral blood of naive B‐PPAR‐ γ −/− mice and control mice (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This finding was in line with the previous report that loss of PPAR‐ γ in B cells did not affect the development of B cells or B‐cell populations, such as pro‐B cells, pre‐B cells, follicular B cells, marginal zone precursor cells, marginal zone cells, among others, in spleen or bone marrow . As reported, mice lacking Breg cells presented with reduced Treg cell frequency . We next investigated the CD4 + CD25 + Foxp3 + Treg cells in peripheral blood and observed no significant change in B‐PPAR‐ γ −/− mice.…”
Section: Discussionmentioning
confidence: 98%